PD‐L1 expression associated with worse survival outcome in malignant pleural mesothelioma. Issue 1 (3rd November 2017) - Nguyen, Bella Hai; Montgomery, Renn; Fadia, Mitali; Wang, Jiali; Ali, Sayed
Abstract: Aim: There is currently a need to identify prognostic biomarkers to assist in a risk adopted approach in treatment of malignant pleural mesothelioma (MPM). Expression of programmed death ligand 1 (PD‐L1) has been studied as a prognostic biomarker in a number of tumors given its central role in antitumoral immune response evasion. Four previously published analyses found PD‐L1 positivity to be an adverse survival prognostic factor in MPM. This study aims to further investigate the relationship between PD‐L1 expression in mesothelioma tissues and survival outcome. Methods: Clinical data of MPM patients from a single institution between 2006 and 2016 were reviewed. Patient's archived tissues were stained with PD‐L1 (Clone Ventana SP263). PD‐L1 positivity was defined as > 1% membranous staining regardless of intensity. Results: Data from fifty eight patients were analyzed. Median age was 73, majority was male (49, 84%) and had ECOG between 0 and 2 (46, 79%). Most common histopathological subtype was epithelioid (42, 72%), 9 (16%) biphasic subtype and 7 (12%) sarcomatoid. Thirty one patients (53%) received best supportive care and twenty seven patients (47%) received chemotherapy or combination treatment. Forty‐two patients had positive PD‐L1 expression (72.4%). The median survival time for PD‐L1 negative group is 15.5 months and 6 months for the positive group. Positive PD‐L1 expression is independently correlated with worse prognosis (HR = 2.02; 95% CI, 1.005–4.057; P ‐value = 0.0484). Conclusions: Our analysis found a higher percentage of MPM patients with positive PD‐L1 (> 1%) compared to other studies. Highly positive PD‐L1 expression was associated with statistically significantly lower median survival time.